Stockmail: stock dashboard website - Azhari, Muhammad Haikal; Nik Salimi, Nik Raeidi; Hassan, Mohd Khairul Azmi (KICT Publishing, 2024)
As the economy of Malaysia is not stable and in growth stage overall, the 2023 growth for the Malaysian economy normalised to 3.7%, following a strong growth registered in the previous year (2022: 8.7%). Growth moderated amid a challenging external environment. Stockmail is a web dashboard built to be useful for traders in providing stock data, predictions and news to help them decide on future trading. The features that will be provided for the app are stock data, the latest stock news data on the stock, expected earnings and currency exchange with real-time currency rates. These features will allow users or traders, especially new traders, to learn useful data and trading skills to gain better profits.